Generation of terahertz radiation from the island films of topological insulator Bi2-xSbxTe3-ySey - K. A. Kuznetsov; G. Kh. Kitaeva; P. I. Kuznetsov; G. G. Yakushcheva (AIP Advances, 2019)
The aim of the research was the studying of the topological insulators Bi2-xSbxTe3-ySey thin films with the different thickness and chemical composition. The obtained time dependences of terahertz radiation have indicated that the generation of THz waves was more efficient in the island film having a total thickness of about tens nanometers with the composition close to the Ren’s curve, where the volume contribution to the conductivity was suppressed. We have demonstrated an amplification of the THz radiation power by applying an external electric field to a topological insulator. This effect can be useful for fabricating photoconductive THz antennas based on topological insulators.